Phase Composition of Mo-Si-V Hypoeutectic Alloys - A V, Larionov; K V, Pikulin; D O, Novikov; V M, Chumarev; L A, Smirnov (KnE Materials Science, 2019)
Thermodynamic modeling (TDM) of phase formation was performed with vanadium doping of the hypoeutectic Mo-Si alloy. It was found that the thermochemical properties of vanadium silicides (presented in the HSC Chemistry 6.12 database), when modeling Mo-Si(14.5-12.2)-V(5.0-20.0) alloys, lead to inadequate results regarding Mo-Si-V diagram state indicators. The simulation results agree satisfactorily with the Mo-Si-V diagram with the following values of ΔH0 298: for V3Si = - 180.4 kJ / mol, for V5Si3 = -433.6 kJ / mol, for VSi2 = -124.5 kJ / mol. According to the results of TDM and X-ray phase analysis (XRD) of the obtained alloys, it was found that vanadium in Mo-Si-V ternary alloys can be found both in the form of silicides, (Mo,V)3Si, and in the composition of the solid solution (Mo,V)